The Integrative Regulatory Network of circRNA, microRNA, and mRNA in Atrial Fibrillation - Jiang, Shengyang; Guo, Changfa; Zhang, Wei; Che, Wenliang; Zhang, Jie; Zhuang, Shaowei; Wang, Yiting; Zhang, Yangyang; Liu, Ban (Frontiers in Genetics, 2019)
Atrial fibrillation (AF) is the most common irregular heart rhythm which influence approximately 1–2% of the general population. As a potential factor for ischemic stroke, AF could also cause heart failure. The mechanisms behind AF pathogenesis are complex and remains elusive. As a new category of non-coding RNAs (ncRNAs), circular RNAs (circRNAs) have been known as the key of developmental processes, regulation of cell function, pathogenesis of heart diseases and pathological responses which could provide novel sight into the pathogenesis of AF. circRNAs function as modulators of microRNAs in cardiac disease. To investigate the regulatory mechanism of circRNA in atrial fibrillation, especially the complex interactions among circRNA, microRNA and mRNA, we collected the heart tissues from three AF patients and three healthy controls and profiled their circRNA expressions with circRNA Microarray. The differentially expressed circRNAs were identified and the biological functions of their interaction microRNAs and mRNAs were analyzed. Our results provided novel insights of the circRNA roles in atrial fibrillation and proposed highly possible interaction mechanisms among circRNAs, microRNAs and mRNAs.